Concise Review: Increasing the Validity of Cerebrovascular Disease Models and Experimental Methods for Translational Stem Cell Research. (24th March 2017) - Boltze, Johannes; Nitzsche, Franziska; Jolkkonen, Jukka; Weise, Gesa; Pösel, Claudia; Nitzsche, Björn; Wagner, Daniel‐Christoph
Abstract: Interspecies differences, anatomical and physiological aspects, as wells as simplified study designs contribute to an overestimation of treatment effects and limit the transferability of experimental results into clinical applications. Confounders of cell therapies for cerebrovascular disorders (CVD) include common CVD comorbidities, frequent medications potentially affecting endogenous and transplanted stem cells, as well as age‐ and immune‐system–related effects. All those can contribute to a substantial modeling bias, ultimately limiting the prospective quality of preclinical research programs regarding the clinical value of a particular cell therapy. In this review, we discuss the nature and impact of most relevant confounders. We provide suggestions on how they can be considered to enhance the validity of CVD models in stem cell research. Acknowledging substantial and sometimes surprising effects of housing conditions, chronobiology, and intersex differences will further augment the translational value of animal models. We finally discuss options for the implementation of high‐quality functional and imaging readout protocols. Altogether, this might help to gain a more holistic picture about the therapeutic impact of a particular cell therapy for CVD, but also on potential side and off‐site effects of the intervention. Stem Cells 2017;35:1141–1153 Abstract : The validity of animal models for cerebrovascular diseases (CVD) such as stroke or vascular dementia is crucial for the success of translational stem cell research. Efforts to enhance both reliability and validity of animal models in translational stem cell research for CVD are highly warranted given the previous failure of the classical neuroprotection paradigm, often considered to be associated with CVD model shortcomings, on one side and the great potential of emerging cell‐based approaches treatments on the other. This paper reviews the most relevant and often neglected confounding factors potentially influencing the impact of (stem) cell transplantations for CVD treatment. The roles of animal models and species‐specific anatomy, sex differences, the adaptive and innate immune systems, chronobiology, comorbidities and cell‐drug interactions are discussed among others. We also suggest potential tools and strategies to improve the predictive value of preclinical research programs on CVD stem cell treatments with respect to their future clinical impact.